AUTHENTICITY OF BEING PORTRAYED BY BEDIL: A BRIEF DESCRIPTION - Muhammad Asif Raza; Hafiz Ahmed Yar; Sami Ullah (Zaban-o-Adab, 2022)
This paper presents the ‘Authenticity of Being’ portrayed by Bedil by describing the existential human condition in relation to the superficial realities of this world. Human person, in everyday life, constructs a pseudo self-based on fulfilling the physical and social conditions of routine life and forgets the real self altogether. So the formation of authentic self is considered the primary human responsibility both in oriental gnostic and occidental philosophical tradition. Bedil pursuits human persons to follow cardinal values based on human devotion and selflessness to transcend from inauthenticity. He considers Passionate Love (Ishq aur Junoon) an enlightened approach for the intuitive experience of Real Self to achieve the ontological meanings and presence of human life.